Impact of a STEAM-SDGs-Based Virtual Reality Mathematics Learning Model on Students’ Critical Thinking and Creativity - Nur Choiro Siregar; Roslinda Rosli; Warsito Warsito; Aris Gumilar (STEAM Journal For Elementary School Education, 2026)
The integration of STEAM (Science, Technology, Engineering, Arts, and Mathematics) and Sustainable Development Goals (SDGs) in higher education has gained increasing attention as a strategy to foster essential 21st-century competencies. In mathematics learning, the use of Virtual Reality (VR) offers immersive and interactive experiences that may enhance higher-order thinking skills. However, empirical evidence examining the impact of a STEAM-SDGs-based VR learning model on students’ critical thinking and creativity remains limited. This study aims to investigate the effect of a STEAM-SDGs-based VR mathematics learning model on students’ critical thinking and creativity. A quantitative research design was employed. The study collected data through structured questionnaires administered to 100 students at Universitas Muhammadiyah Tangerang. The proposed research model was analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS version 3 to evaluate both measurement and structural models. The findings indicate that the STEAM-SDGs-based VR learning model has a significant positive effect on students' critical thinking and creativity. The immersive VR environment, combined with interdisciplinary STEAM integration and SDGs-oriented problem contexts, contributes to improved analytical reasoning, idea generation, and innovative problem-solving skills. This research provides empirical support for integrating STEAM, the SDGs, and Virtual Reality into mathematics education at the higher education level. The study contributes to the development of innovative, technology-enhanced learning models that promote critical thinking and creativity, offering practical implications for educators and policymakers seeking to strengthen 21st-century competencies in university settings.